Unraveling The Influence of Factors on Micro Small and Medium-Sized Enterprises’ Adoption of Social Media Marketing and Its Business Impact - Steven Young; J. Johny Natu Prihanto; Prio Utomo (Return : Study of Management, Economic and Bussines, 2023)
The continuously growing opportunities in the digital economy have prompted the Indonesian government to encourage Micro, Small, and Medium-sized Enterprises (MSMEs) to undergo digital transformation. While there are various approaches available, marketing products/services through social media is believed to be one of the most effective methods. To maximize the benefits of social media marketing adoption for MSMEs, it is indeed crucial to identify the influential factors related to its adoption. Therefore, this study aims to quantitatively identify the factors influencing social media adoption among MSMEs in Indonesia. In this study, attention is directed toward five factors: performance expectancy, social influence, effort expectancy, facilitating conditions, and operating costs. The study incorporated 136 actively participating MSMEs that employed social media marketing. We opted to employ Partial Least Squares Structural Equation Modeling (PLS-SEM) due to its suitability for our sample size and potential data characteristics. As we were unsure about the normality of our data and the presence of measurement issues, PLS-SEM provided a robust and flexible approach. It allows us to analyze complex models and handle potential non-normal data and measurement concerns, ensuring reliable results even if such issues arise. Data is processed using the SmartPLS 3.0 software. The research findings indicate that the usage of social media marketing is influenced by performance expectancy and social influence. However, factors such as effort expectancy, facilitating conditions, and costs do not have a significant impact on social media adoption among MSMEs. Furthermore, the results of the study highlight the positive impact of utilizing social media for marketing on the performance of MSMEs, particularly in terms of increasing sales, enhancing customer relationships, improving productivity, and fostering creativity. These findings suggest that MSMEs can leverage social media platforms to achieve tangible benefits and enhance various aspects of their business operations.